Exposures and cancer incidence near oil fields in the Amazon basin of Ecuador. Issue 8 (1st August 2001) - Sebastián, M San; Armstrong, B; Córdoba, J A; Stephens, C
Abstract : OBJECTIVES: To examine environmental exposure and incidence and mortality of cancer in the village of San Carlos surrounded by oil fields in the Amazon basin of Ecuador. METHODS: Water samples of the local streams were analyzed for total petroleum hydrocarbons (TPHs). A preliminary list of potential cancer cases from 1989 to 1998 was prepared. Cases were compared with expected numbers of cancer morbidity and mortality registrations from a Quito reference population. RESULTS: Water analysis showed severe exposure to TPHs by the residents. Ten patients with cancer were diagnosed while resident in the village of San Carlos. An overall excess for all types of cancer was found in the male population (8 observed v 3.5 expected) with a risk 2.26 times higher than expected (95% confidence interval (95% CI) 0.97 to 4.46). There was an overall excess of deaths for all types of cancer (6 v 1.6 expected) among the male population 3.6 times higher than the reference population (95% CI 1.31 to 7.81). CONCLUSIONS: The observed excess of cancer might be associated with the pollution of the environment by toxic contaminants coming from the oil production.